'Solve he equation: X^2/3 = 2X^1/3'

Now understand X^2/3 = Cube root( X)^2 and 2X^1/3 = cube root(2x)

My next line of thinking was to get rid of the cube roots, by cubing each side, so:

X^2 = 2X

Solving this to 0, I get X(X+2)=0

So X= 0 and X=-2

Substituting these values back into the equation, 0^2/3 = 2(0)^1/3 so 0 = 0, meaning 0 is a solution

However, I don't know I that answer was purely conidial as cube root (4) =Cube root (-4), when the answers are X = 0 and X = 8.

If anybody can explain where I have gone wrong, it would be greatly appreciated.